Nuts, anchor, self-locking, floating, self-aligning, two lug, with MJ threads, classifications: 900 MPa (at ambient temperature)/235°C, 900 MPa (at ambient temperature)/315°C, 900 MPa (at ambient temperature)/425°C. Dimensions. (15th October 1997) - British Standards Institution,
No abstract available